Islamophobia Discourse: Analyzing the Representation of Islam and Muslims in Public Narratives - Tamamiyah, Lutfiyatut (Islamic Journal of Communication and Public Discourse, 2025)
The phenomenon of Islamophobia has become a rapidly growing global issue, reinforced by negative representations of Islam and Muslims in public narratives, both through traditional and social media. These representations shape public perceptions that often associate Muslims with violence and extremism, exacerbating social tensions between communities. This study aims to analyze the patterns of representation of Islam and Muslims in traditional media and social media and identify differences in the characteristics of narratives on both platforms. The method employed is a qualitative approach based on critical discourse analysis (CDA), utilizing data from 200 traditional media articles and 100,000 social media posts related to Islam and Muslims between 2020 and 2025. Analysis was conducted using NVivo 14 software to code themes, sentiments, and narrative framing. The results showed that negative representations dominated, with 50% of traditional media news and 70% of social media posts portraying Islam negatively. The findings support Cultivation and Framing theories, which state that exposure to media content shapes long-term social perceptions. The implications of this study emphasize the importance of media literacy, reforming journalistic ethics, and developing community-based counter-narratives to reduce the spread of Islamophobia and foster fairer representations of Muslims in the public sphere.